Voice as Entry to Agriculturalists' Conservationist Identity: A Cultural Inventory of the Yellowstone River. Issue 5 (3rd September 2017) - Horton, Cristi; Hall, Damon; Gilbertz, Susan; Peterson, Tarla
ABSTRACT: We explored the communicative construction of a conservationist identity among primary producers by excavating voices of agriculturalists operating along the Yellowstone River (Montana, USA). We used a cultural inventory approach to discover and then listen to informants' voices as they constructed their conservation identity. Those who self-identified as conservationists talked about their ecological and social responsibilities, and described challenges they faced in protecting individual resources and system processes of the watershed. For these agriculturalists, conservation and production are inextricably linked, and enable them to provide a sustainable resource base for future generations. Insight from these voices enhances understanding of what sustainability could mean to those who self-identify as both conservationists and primary producers.